A systematic integrated technique for developing subject matter competencies in pharmacy education. - Sauve, Jenna; Battistella, Marisa; Ho, Certina; Austin, Zubin (International Journal of Pharmacy Practice, 2026)
The article focuses on a systematic approach for developing subject matter competencies in pharmacy education to guide curriculum design amid expanding pharmacist roles and static curriculum time. It proposes a three-phase methodology combining a scoping review, expert and stakeholder consultation, and a modified hybrid Delphi panel—a consensus-generating technique involving pharmacy and interprofessional experts—to create evidence-informed, consensus-based competency frameworks. This approach aims to enhance curriculum consistency, incorporate diverse perspectives including patients and marginalized groups, and optimize teaching and assessment strategies. The method is particularly suited for clinical and health system-related content requiring expert input and supports pharmacy educators in addressing evolving educational needs within limited instructional time.